China’s Framing of Development in the Context of the Belt and Road Initiative : A case study of the China-Laos Railway - Tombelli, Bianca (My University, 2025)
This thesis explores how the China-Laos railway is represented in the articles of the English-language newspaper China Daily and within the broader context of the Belt and Road Initiative (BRI). Through a qualitative approach, based on Critical Discourse Analysis (CDA), the study examines how China Daily frames the railway project, investigating how such framing contributes to constructing a particular conceptualization of ‘development’ and to what extent it reflects dominant discourses and theories of development.
Keywords: Belt and Road Initiative, China-Laos Railway, Development, Media Framing, China Daily, Critical Discourse Analysis